1988
DOI: 10.1038/clpt.1988.211
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin pharmacokinetics in critically ill trauma patients

Abstract: Preliminary data have suggested that phenytoin systemic clearance may increase during initial therapy in critically ill patients. The objectives for this study were to model the time-variant phenytoin clearance and evaluate concomitant changes in protein binding and urinary metabolite elimination. Phenytoin was given as an intravenous loading dose of 15 mg/kg followed by an initial maintenance dose of 6 mg/kg/day in 10 adult critically ill trauma patients. Phenytoin bound and unbound plasma concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…For example, acute inflammation alters alpha-2 globulin expression and other trace element binding proteins [23]. Certain drugs also exhibit lower plasma protein binding rates in patients with critical illness and renal failure than in healthy individuals [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, acute inflammation alters alpha-2 globulin expression and other trace element binding proteins [23]. Certain drugs also exhibit lower plasma protein binding rates in patients with critical illness and renal failure than in healthy individuals [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the fact that the median apparent clearance of tirilazad in head-injured patients not receiving anticonvulsants in the present study (0.258 L/h/kg) is somewhat lower than that observed previously in healthy male volunteers at the same dose level (0.352 L/h/kg). 15 Previous work by Boucher et al 17,18 suggests that the clearances of antipyrine and phenytoin were increased following acute neurotrauma. In the present study, tirilazad clearance did not appear to be induced following acute head trauma.…”
Section: Discussionmentioning
confidence: 96%
“…Serial (prior to the dose, at the end of the infusion, and 1, 3, and 5 h after infusion start) venous blood samples (5 mL) were collected after the first or second dose and after one of the doses on the last dosing day (doses [17][18][19][20]. Nadir samples were also collected on days 2-4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in Vma x in group 2 could be due to metabolic induction, as has been suggested in a case report of a patient with low phenytoin concentrations who was receiving total parenteral nutrition [28] and as is also suggested by the metabolite data of the current study. Results of another study have shown increased estimates of Vma x for phenytoin in critically ill patients [29]. It was suggested that changes in protein binding, induction of hepatic metabolism or stressrelated transient increases in hepatic function could all possibly play a part in the increased elimination rate of phenytoin.…”
Section: Discussionmentioning
confidence: 98%